Speaking Infinities : God and Language in the Teachings of Rabbi Dov Ber of Mezritsh - Mayse, Ariel Evan (Book collections on Project MUSE., 2020)
In Speaking Infinities, Ariel Evan Mayse explores the life and work of the Hasidic figure Rabbi Dov Ber Friedman of Mezritsh (1704-1772) to elucidate his theory of language in which all human tongues, even in their mundane forms, have the potential to become sacred when returned to their divine source.